Practice variability among the EMS systems participating in Cardiac Arrest Registry to Enhance Survival (CARES) - Govindarajan, Prasanthi; Lin, Lisa; Landman, Adam; McMullan, Jason T.; McNally, Bryan F.; Crouch, Allison J.; Sasson, Comilla (Resuscitation, 2012)
To describe the demographic, organizational and provider characteristics of the Emergency Medical Services (EMS) agencies participating in the Cardiac Arrest Registry to Enhance Survival (CARES). A web based survey instrument was developed by the CARES investigators and distributed to the EMS agencies participating in CARES in 2008. Survey questions addressed three domains related to prehospital care: (1) descriptors of the participating EMS agencies, (2) methods of clinical care and clinical protocols used by EMS agencies to deliver out-of-hospital cardiac arrest care and (3) use of resuscitation techniques by EMS agencies. Survey responses were collated and analyzed using descriptive statistics. Surveys were received from 21/25 (84%) sites. The EMS agency characteristics including the response areas served by the agencies, organizational structure, medical direction status and deployment status are described. All respondents were non-volunteer agencies with a large number of them being fire-based (43%). Significant variability among the communities was observed with respect to their medical direction status and deployment status. We also observed differences in the management of OHCA among the participating agencies which included implementation of ACLS guideline updates, presence of termination of resuscitation protocol and destination policies for OHCA subjects. Similar variations between agencies were also observed in the use of resuscitation techniques. Differences were observed between the EMS agencies participating in CARES. The clinical impact of these observed differences in agency and provider characteristics on OHCA outcomes deserves study.